Diagenetic Fluid and Its Impact on Sandstone Reservoirs in the Southern Boxing Sag, Dongying Depression, Bohai Bay Basin, China - Zhenhuan Shen; Zhuang Ruan; Bingsong Yu; Shujun Han; Chenyang Bai; Qiuhong Chang; Tianxia An (Geofluids)
Diagenesis typically exerts a crucial impact on the formation of high-quality sandstone reservoirs in the Eocene Shahejie Formation, Dongying Depression. To better understand the formation process of petrophysical properties, this research conducts petrographic and geochemical analyses to investigate the nature of diagenetic fluids. Petrographic observations suggest that the dominant cements are carbonate, authigenic quartz, and clay minerals, accompanied with the dissolution of feldspar and calcite. The homogenization temperature of aqueous inclusions in quartz overgrowth usually exceeds 90°C corresponding to the maturity of organic matter. Quartz overgrowths contain higher amounts of CaO and Al2O3 than detrital quartz. This indicates that the siliceous fluid mainly originates from the dissolution of feldspar. Moreover, the conversion of clay minerals also provides trace amounts of silica into pore water during the burial process. Carbonate cements consist of early-stage calcite as well as late-stage Fe-calcite and ankerite. Calcite with relatively higher MnO proportions shows yellow luminescence and dissolution signs. Fe-calcite and ankerite cements have a higher homogenization temperature than that of quartz overgrowth and mainly concentrate in FeO and MgO as well as contain a small amount of Na+, K+, and Sr2+. The rare earth element (REE) pattern of bulk mudstone and carbonate cements as well as C–O isotopic evidences indicate that the diagenetic fluids of carbonate cementation are primarily controlled by the adjacent mudstone, whereas mineral dissolution and altered clay minerals in sandstone provide additional cations for the local reprecipitation of late-stage carbonate. Therefore, diagenetic fluids within sandstone reservoirs are typically subject to alkaline–acid–alkaline conditions and are influenced by internal sources in a closed system. Compaction significantly reduces the pore space of sandstone reservoirs in the Boxing Sag. Carbonate cementation further increases the complexity of pore structure and obeys the principle of mass balance.